2010
DOI: 10.1021/ja100245d
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Polymerization of a Suspended Planar Bilayer Creates a Fluid, Highly Stable Membrane for Ion Channel Recordings

Abstract: Suspended planar lipid membranes (or black lipid membranes (BLMs)) are widely used for studying reconstituted ion channels, although they lack the chemical and mechanical stability needed for incorporation into high-throughput biosensors and biochips. Lipid polymerization enhances BLM stability but is incompatible with ion channel function when membrane fluidity is required. Here we demonstrate the preparation of a highly stable BLM that retains significant fluidity by using a mixture of polymerizable and nonp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 62 publications
4
61
0
1
Order By: Relevance
“…55 Following further accumulation of monomers, voltage-gated activity (Figure 6C) was observed, which agreed well with previous observations. 56 The observation of voltage-gated alamethicin activity further supported the presence of a lipid bilayer, and demonstrated that the bilayer was sufficiently fluid to allow normal alamethicin activity. These results suggest that the physiology of bilayers formed on planar SU-8 apertures will prove suitable for studies of other dynamic transmembrane protein systems, and will facilitate the development of new ligand-gated ion channel-based sensing technologies.…”
Section: Resultsmentioning
confidence: 82%
“…55 Following further accumulation of monomers, voltage-gated activity (Figure 6C) was observed, which agreed well with previous observations. 56 The observation of voltage-gated alamethicin activity further supported the presence of a lipid bilayer, and demonstrated that the bilayer was sufficiently fluid to allow normal alamethicin activity. These results suggest that the physiology of bilayers formed on planar SU-8 apertures will prove suitable for studies of other dynamic transmembrane protein systems, and will facilitate the development of new ligand-gated ion channel-based sensing technologies.…”
Section: Resultsmentioning
confidence: 82%
“…However mixtures of poly(bis-DenPC) and a nonpolymerizable lipid such as diphytanoyl phosphatidylcholine are sufficiently fluid to support alamethicin activity. 31 …”
Section: Resultsmentioning
confidence: 99%
“…Pipet fabrication and modification were described previously 23, 24. Briefly, borosilicate capillaries were pulled to a sharp tip using a micropipet puller, then broken to an opening of ca.…”
Section: Methodsmentioning
confidence: 99%